Capitalism, Neoliberalism, and Unfree Labour. (September 2019) - Gordon, Todd
The literature on the unfree character of temporary migrant labour has drawn much needed attention to the poor working conditions faced by migrant workers and opened up an important space to challenge those ubiquitous claims by defenders of the current political-economic status quo of the freedom expressed at the core of neoliberalism. However, there is a risk to focusing on legal unfreedom to the exclusion of a broader critique of the logic of capitalist reproduction, the very premise of which is the private ownership of society's productive wealth and the alienation of the majority of people from that wealth. Unfreedom and coercion are systematic to capitalist market relations, and all wage labour, including that of formally 'free', is unfree. This article examines different conceptions of labour unfreedom and concludes with a discussion of unfree labour in the neoliberal context.